Improving National Trauma Data Bank® coding data reliability for traumatic injury using a prospective systems approach - Ewing, Michael; Funk, Geoffrey A; Warren, Ann Marie; Rapier, Nakia; Reynolds, Megan; Bennett, Monica; Mastropieri, Cyndi; Foreman, Michael L (Health informatics journal, 2016)
Trauma centers manage an active Trauma Registry from which research, quality improvement, and epidemiologic information are extracted to ensure optimal care of the trauma patient. We evaluated coding procedures using the Relational Trauma Scoring System to determine the relative accuracy of the Relational Trauma Scoring System for coding diagnoses in comparison to the standard retrospective chart-based format. Charts from 150 patients admitted to a level I trauma service were abstracted using standard methods. These charts were then randomized and abstracted by trauma nurse clinicians with coding software aide. For charts scored pre-training, percent correct for the trauma nurse clinicians ranged from 52 to 64 percent, while the registrars scored 51 percent correct. After training, percentage correct for the trauma nurse clinicians increased to a range of 80-86 percent. Our research has demonstrated implementable changes that can significantly increase the accuracy of data from trauma centers.